Understanding the drivers of sustainable entrepreneurial practices in Pakistan's leather industry: A multi-level approach. Issue 2 (12th October 2017) - Wahga, Aqueel Imtiaz; Blundel, Richard; Schaefer, Anja
Abstract : Purpose: The purpose of this paper is to analyse the drivers of sustainable entrepreneurial practices in SMEs operating in a developing economy. The secondary objectives are to explore the relationship between these drivers and to draw out the implications for policy and practice. Design/methodology/approach: The paper is informed by the literature on sustainable entrepreneurship, and on the drivers of pro-environmental practices in SMEs. It reports on the results of an intensive multi-level empirical study, which investigates the environmental practices of SMEs in Pakistan's leatherworking industry using a multiple case study design and grounded analysis, which draws on relevant institutional theory. Findings: The study identifies that coercive, normative and mimetic isomorphic pressures simultaneously drive sustainable entrepreneurial activity in the majority of sample SMEs. These pressures are exerted by specific micro-, meso- and macro-level factors, ranging from international customers' requirements to individual-level values of owners and managers. It also reveals the catalytic effect of the educational and awareness-raising activities of intermediary organisations, in tandem with the attraction of competitiveness gains, (international) environmental regulations, industrial dynamism and reputational factors. Practical implications: The evidence suggests that, in countries where formal institutional mechanisms have less of an impact, intermediary organisations can perform a proto-institutional role that helps to overcome pre-existing barriers to environmental improvement by sparking sustainable entrepreneurial activity in SME populations. Originality/value: The findings imply that the drivers of sustainable entrepreneurial activity do not operate in a "piecemeal" fashion, but that particular factors mediate the emergence and development of other sustainability drivers. This paper provides new insights into sustainable entrepreneurship and motivations for environmental practices in an under-researched developing economy context.